The role of Sangguniang Kabataan in policy-making in Santa Barbara, Iloilo (1996-2001). - Sorupia, Maynaquita S
The study aimed at achieving the following objectives 1.) To trace the historical foundation of the Sangguniang Kabataan in the Philippines 2.) To know the role of SK in policy-making 3.) To identify policies that the SK had formulated and 4.) To assess the effectivity of the formulated policies in terms of program and projects those were geared towards youth development., Research methods that were employed in gathering the data needed for the study were personal interviews with the local Legislative Council officials and questionnaires. Library research was also utilized to gather necessary data, especially in the offices of the Department of the Interior and Local Government as well as in the Municipal Planning and Development.Findings of the study revealed that the institutionalization of the youth's representation in the sanggunian thru the Sangguniang Kabataan (legislative council) in the Municipality of Santa Barbara had made a little impact in representing the youth's desire and aspirations in the sangguniang and other governmental affairs. Reasons could be attributed to the lack of coordination initiative and unity among the youth. The ideal and real goal of the SK in representing the youth in the Council has yet to be realized and achieved.